2021
DOI: 10.1515/ntrev-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and thermoelectric properties in 3D macroscopic pure carbon nanotube materials

Abstract: Sintered carbon nanotube (CNT) blocks and porous CNT sponges were prepared, and their thermoelectric properties were measured. The maximum dimensionless thermoelectric figure-of-merit, ZT, at room temperature of the sintered single-walled carbon nanotube (SWCNT) block is 9.34 × 10−5, which is twice higher than that of the sintered multi-walled carbon nanotube (MWCNT) block in this work and also higher than that of other sintered MWCNT blocks reported previously. In addition, the porous MWCNT sponge showed an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…"φ p " was reported as 0.0005, 0.001, 0.0003, and 0.002 for the PVC/MWCNT, PET/MWCNT, epoxy/SWCNT, and PC/ABS/MWCNT samples, respectively. These levels were compared with the predictions of Equation (15). The values of (t, τ) were obtained as (1.5, 400), (3, 300), (7,145), and (8, 1600) (nm, S/m) for the PVC/MWCNT, PET/MWCNT, epoxy/SWCNT, and PC/ABS/MWCNT samples, respectively.…”
Section: Comparison Between Predictions and Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…"φ p " was reported as 0.0005, 0.001, 0.0003, and 0.002 for the PVC/MWCNT, PET/MWCNT, epoxy/SWCNT, and PC/ABS/MWCNT samples, respectively. These levels were compared with the predictions of Equation (15). The values of (t, τ) were obtained as (1.5, 400), (3, 300), (7,145), and (8, 1600) (nm, S/m) for the PVC/MWCNT, PET/MWCNT, epoxy/SWCNT, and PC/ABS/MWCNT samples, respectively.…”
Section: Comparison Between Predictions and Experimental Datamentioning
confidence: 99%
“…Carbon nanotubes (CNTs) endow significant conductivity and high mechanical properties to composites, especially polymer CNT nanocomposites (PCNT) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. A CNT aspect ratio in a range of 500–1000 creates a conductive network at extremely low concentrations of CNTs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zhang et al [ 30 ] fabricated Bucky paper (prepared with the pressing of highly aligned CNT films) with a density of 1.39 mg/cm 3 , and the thermal conductivity reached 766 W/m·K. Yang et al [ 31 ] performed 3D microscopic analysis of SWCNTs, MWCNTs, and an MWCNT sponge. They concluded that the density of CNTs has a significant effect on thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The unexpectedly low thermal conductivities of CNT networks were verified later by other groups. [4][5][6] For example, Yang et al [4] demonstrated that the thermal conductivity of single-walled CNT (SWCNT) networks is 0.142 W/(m•K), and can be reduced further to 0.057 W/(m•K) as the density of networks reduces from 0.217 g/cm 3 to 0.097 g/cm 3 .…”
mentioning
confidence: 99%
“…This ultralow thermal conductivity of CNT networks has been attributed to both the large contact thermal resistance between CNTs and the high porosity of CNT networks. [3][4][5] When only the porosity is considered, the thermal conductivity of a CNT network k net can be written as [3,7]…”
mentioning
confidence: 99%